Diseño de normativa para el mejoramiento de la gestión académica en la Pontificia Universidad Católica del Ecuador sede Santo Domingo, año 2014. - Chimbo Auquilla, Patricio (2014)
The development of the research has been a valuable contribution to the PUCE SD, because it has allowed developing regulations that will improve the quality of service on the Academic Board. Starts in academic management research universities in the world, national and local; It continues with a description of the organization, which discloses its activities and aims of the academy; after this, a field study was performed to managers, academic administrators and professors, in order to know the level of satisfaction perceived in these classes relating to management; proceeds with the proposed rule that reflects the views to be applied by units that are directly related to this activity; eventually research findings with relevant recommendations are drawn.